Articles The comparative study on retention rate and caries prevention between Glassionomer and Resin using as pit and fissure sealant in mobile dental service, Buriram province. - ทิพย์สุนทรชัย จีรศักดิ์ (Thai Dental Public Health Journal, 2003)
The objective of this study was to evaluate the retention rate and dental caries rate after sealing with resin and glassionomer for decision making of choosing the proper sealant material used in mobile dental service. Randomized controled trial study was prepared, The sample were 120 children age of 6 - 7 year, the first 60 children received glassionomer sealing at #36 and resin sealing at #46 and the other group was sealed opposite. No treatment was prepared in the opposite teeth for comparing the dental caries rate. Follow up at 1 and 2 year, Using chi-square for analysis. The percentage of the first and second year data collecting showed as 89.16 and 84.16 respectively. The retention rate of resin and glassionomer at 1 year are 19.6% and 22.42% respectively. At 2 years, there were 8.9% and 12.8% respectively and no significant statistical difference (P > 0.05) The caries rate at 1 year of resin and glassionomer group were 24.3% and 12.1% respectively, at the second year were 44.55% and 20.80% respectively, there was significant statistical difference at P < 0.05 as the resin sealed teeth had higher dental caries rate two times than glassionomer sealed teeth. At 1 year dental caries rate of upper teeth was 36.9% and the lower teeth was 18.2%. There was significant statistical difference (P < 0.05) as the upper teeth had higher dental caries rate two times than the lower one. However at 2 years, there was no significant statistical difference. The factors that affected to retention rate of the two materials were operators, moisture, effectiveness of equipment. The lower dental caries rate of glassionomer sealed teeth group might have come from the influence of fluoride substance in glasionomer material that useful for dental caries prevention.